Sentence to hope : a Saʻdallah Wannous reader - Wannūs, Saʻd Allāh, 1941-1997 (Margellos world republic of letters book., 2019)
The first major English language collection of plays and essays by Syrian playwright Sa'dallah Wannous. Sa'dallah Wannous is acknowledged to be one of the Arab world's most significant playwrights, writers, and intellectuals of the twentieth century. This is the first major English language collection that brings together his most significant plays and essays. Selections include the groundbreaking 1969 play An Evening's Entertainment for the Fifth of June, a scathing indictment of the duplicity of Arab leaders during the 1967 War, as well as Wannous's most celebrated play, Rituals of Signs and Transformations, a bold treatment of homosexuality, prostitution, clerical corruption, and the quest for female liberation. In addition to his work as a playwright, Wannous, like Brecht, was an astute theatrical and cultural critic, and his essays, some of which are included here, offer shrewd diagnoses of the ills of Arab society and the essential role of theater in ameliorating them.